Lockdown and return to performance: caution with the shoes! - Morin, J.-B. (2020)
Progressive return to sport and increase in mechanical load: it's gotta be (also) the shoes (and other sport-specific material) For example in football, rugby, cycling, sprint, jump etc: going back to ~daily use after 8+ wks without might be risky If still locked down, use them regularly for home sessions to maintain specific stimulus.